2008
DOI: 10.1007/s00424-008-0448-y
|View full text |Cite
|
Sign up to set email alerts
|

Probing nanomechanical properties from biomolecules to living cells

Abstract: Atomic force microscopy is being increasingly used to explore the physical properties of biological structures. This technique involves the application of a force to the sample and a monitoring of the ensuing deformation process. The available experimental setups can be broadly divided into two categories, one of which involves a stretching and the other an indentation of the organic materials. In this review, we will focus on the indentation technique and will illustrate its application to biological material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 97 publications
0
70
0
Order By: Relevance
“…The obtained mean Young modulus values were of 0.7 ± 0.5 kPa and 1.2 ± 0.4 kPa, correspondingly (data calculated from Gaussian fit, for the indentation depth of 500 nm). Cell indentation generates the response from inner structural cell components [13]. For small indentations depths the values of the modulus are dominated by the mechanical properties of the cell membrane.…”
Section: Estimation Of the Energy Dissipationmentioning
confidence: 99%
“…The obtained mean Young modulus values were of 0.7 ± 0.5 kPa and 1.2 ± 0.4 kPa, correspondingly (data calculated from Gaussian fit, for the indentation depth of 500 nm). Cell indentation generates the response from inner structural cell components [13]. For small indentations depths the values of the modulus are dominated by the mechanical properties of the cell membrane.…”
Section: Estimation Of the Energy Dissipationmentioning
confidence: 99%
“…Moreover, such measurements can be performed seamlessly in physiological conditions and in presence of different liquid media. This versatility is reflected in the AFM literature which presents with increasing frequency novel results regarding mechanical properties of single cells, bacteria or even single molecules (Berquand et al, 2010;Kasas and Dietler, 2008). At a cellular scale, it has been demonstrated that the mechanical properties of the membrane can reflect the physiological state of the entire system and that these properties are clearly altered in the occurrence of pathological conditions (Cross et al, 2007;Girasole et al, 2010;Lekka et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Protein complexes and their network of interactions in cellular function and regulation are at the forefront of biological research [55]. Structural biology methods provide three-dimensional atomic architectures of proteins that provide insights into physiological function, but other factors such as chemical composition, electrical charge distribution, and mechanical properties are also important [56]. Proteins acquire their unique biological functions through folding of their peptides into a unique and stable three-dimensional structure.…”
Section: Mechanically Unfolding Membrane Proteins With Smfsmentioning
confidence: 99%